Pengaruh Panjang dan Diameter Stek Batang Terhadap Pertumbuhan Bibit Kelor (Moringa oleifera Lam.) - Wahyu Astiko; Ahsani Taqwim; Bambang Budi Santoso (LPPM Universitas Mataram, 2018)
The purpose of the study is to discover the best length and the diameter of Moringa oleifera Lam. stem cuttings to produce high quality of seedlings. The study was conducted during March-May 2017 located in the nursery field at Dasan Agung, Mataram, 16 m asl. This study was experimental research with Complete Randomized Design with three three replications, and each contains 5 serial experiment units. The treatment for stem cutting length (25 cm, 50 cm, and 75 cm) was then combined with different stem cutting diameters (3-4 cm, 4.1-5 cm, and 5.1-6 cm). The result shows that combination of 75 cm stem length with stem diameter of 5.1-6 cm resulted to have the best seedling growth.The longer the cutting (up to 75 cm), the better the growth of the seedling. The thickest stem diameter (5.1-6 cm) resulted better seedling